Multi Gigabit Wireless Data Transfer in Detectors at Future Colliders - Brenner, R.; Dehos, C.; Locci, E. (Frontiers in Physics, 2022)
The WADAPT (Wireless Allowing Data And Power Transmission) consortium has been formed to identify the specific needs of different projects that might benefit from wireless communication technologies with the objective of providing a common platform for research and development in order to optimize effectiveness and cost. Wireless technologies have developed extremely fast over the last decade and are now mature enough to be a promising alternative to cables and optical links, with a possibility of revolutionizing detector design. Although wireless readout has the qualities and properties to be used in many collider detectors, this article focuses on the transmission of large amount of data from vertex detectors at high rate, low power budget and in potential high radiation environment. For vertex detectors, the 60 GHz band has proven to be adequate and commercial products are already available, providing 6 Gbps data links. This technology allows efficient partitioning of detectors in topological regions of interest, with the possibility of adding intelligence on the detector to perform four-dimensional reconstruction of the tracks and vertices online, in order to attach the tracks to their vertex with great efficiency even in difficult experimental conditions, and conveniently substitutes a mass of materials (cables and connectors). Early transceiver module products have been successfully tested for signal confinement, crosstalk, electromagnetic immunity and resistance to radiation. In the long run, emerging 140 GHz bands could also be used for higher data rates (>100 Gbps) at future high energy and luminosity hadron colliders.